(untitled) (American Journal of Life Science and Innovation, 2024)
Testicular cancer is a relatively rare but significant malignancy, primarily affecting males between the ages of 15 and 35. The incidence and epidemiological patterns of testicular cancer vary across different geographic regions. This study aims to describe the demographics and outcomes of testicular tumors in patients treated in a tertiary setting at King Faisal Specialist Hospital and Research Centre in Riyadh. This retrospective cohort study was conducted at King Faisal Specialist Hospital and Research Centre (KFSHRC), focusing on patients across various regions in the kingdom from 2000 to 2017. The research offers a comprehensive retrospective analysis. The records of 125 males diagnosed and treated with testicular cancers with an age bracket of 14-35 years were examined. It was observed that males aged 26-35 showed the highest rate of incidence of testicular cancer. The primary differences between the progression of seminomas and nonseminomas are explored, with the latter comprising diverse subtypes such as yolk sac tumors, teratomas, embryonal carcinomas, and choriocarcinomas. This research studied patient demographics, clinical presentations, histopathological patterns, treatment modalities, and associated complications. Apart from stage 3 cases, the present research found consistency in survival outcomes, recurrence rates, and risk variables across locations. This retrospective cohort study challenges long-held beliefs and offers new insight into the treatment and prognosis of patients with testicular cancer at the KFSHRC. This study is significant because it has the potential to influence future methods of treating testicular cancer and advance knowledge of the subtleties and regional variations of the illness, which is beneficial for both patients and healthcare professionals.